Allogeneic Hematopoietic Cell Transplant for Systemic Juvenile Idiopathic Arthritis and Macrophage Activation Syndrome - Davidson, Nicole; Rangarajan, Hemalatha G.; Driest, Kyla; Bajwa, Rajinder P. S.; Polishchuk, Veronika; Abu-Arja, Rolla F. (Case Reports in Rheumatology, 2021)
Systemic juvenile idiopathic arthritis (sJIA) is characterized by arthritis, fever, rash, lymphadenopathy, hepatosplenomegaly, and serositis. Macrophage activation syndrome is the most feared complication of sJIA with a high risk of mortality. We report a 16-year-old female diagnosed with refractory systemic juvenile idiopathic arthritis (sJIA) complicated by recurrent macrophage activation syndrome (MAS), severe joint disease, and lung involvement requiring prolonged immunosuppressive therapy. She received a matched unrelated allogeneic hematopoietic cell transplant (Allo-HCT) using a reduced-intensity conditioning regimen and is now, 3 years after the transplant, with complete resolution of sJIA symptoms, off immunosuppressants, and with significant improvement in the quality of life.